Čtení ručkového měřicího přístroje pomocí kamery - Běloch, Miroslav; Miroslav Běloch (České vysoké učení technické v Praze, 2020)
Tato práce navrhuje řešení pro čtení analogového měřicího přístroje pomocí kamery. Záměrem je, aby byl výsledek použitelný na různých typech měřičů. Program nejdříve detekuje region displaye, ve kterém následně hledá stupnici s ručičkou. Dále bylo naším cílem, aby byl systém do jisté míry odolný vůči vnějším vlivům jako posunutí kamery nebo snížení intenzity světla. Na závěr je návrh realizován a experimentálně ověřen pomocí platformy Raspberry Pi.

This thesis proposes a solution for an analog measuring device reading using camera. The objective is for the system to be applicable on different types of panel meters. First it detects the region of the display, in which it then searches for the scale marks and the pointer. Eventually the reading is obtained by the comparison of scale marks and the pointer. Furthermore, the system is designed to be resistant to some extend to external influences such as device shifts, rotation or reduced illumination. The project is then implemented with Raspberry Pi and the accuracy is verified by the means of measuring of various scenarios.
Reading of an Measuring Device Using Camera
Keywords: analogový měřicí přístroj; čtení; počítačové vidění; Raspberry Pi; rozpoznávání; analog meter; computer vision; Raspberry Pi; reading; recognition